2008
DOI: 10.1038/sj.bjc.6604790
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of fulvestrant as an extra step in the treatment sequence for ER-positive advanced breast cancer

Abstract: Drug therapies for advanced breast cancer in hormone-receptor-positive disease include both hormonal and chemotherapies. Current UK practice is to minimise toxicity by using sequential hormonal agents for as long as clinically appropriate. A Markov model was developed to investigate the cost effectiveness of different sequences of therapies, particularly exploring the effects of adding an additional hormonal agent, fulvestrant, to the treatment pathway. A systematic review was undertaken and a panel of seven U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Fulvestrant was found to be a cost-effective treatment alternative in ER+ ABC at a lower dose of 250 mg. The cost effectiveness of a second-line treatment sequence with and without fulvestrant 250 mg was assessed in Germany [ 45 ] and the UK [ 46 ]. Both studies concluded that fulvestrant 250 mg is a valuable ET in ABC, leading to cost savings in the German study and an ICER of £7500/QALY in the UK study.…”
Section: Discussionmentioning
confidence: 99%
“…Fulvestrant was found to be a cost-effective treatment alternative in ER+ ABC at a lower dose of 250 mg. The cost effectiveness of a second-line treatment sequence with and without fulvestrant 250 mg was assessed in Germany [ 45 ] and the UK [ 46 ]. Both studies concluded that fulvestrant 250 mg is a valuable ET in ABC, leading to cost savings in the German study and an ICER of £7500/QALY in the UK study.…”
Section: Discussionmentioning
confidence: 99%
“…Decision models that start at the point of diagnoses are more likely to reflect the complete sequence of treatments used in chronic conditions, for example, some studies of biologics in rheumatoid arthritis developed the decision population within the actual model, with patients entering the model being newly diagnosed with early disease [67,75,83,85,99,122]. However, the likelihood that there is no matching evidence is increased, and more assumptions are required.…”
Section: Simplifying Assumptions Regarding Sequences Of Treatmentmentioning
confidence: 99%
“…66,67 Second-line therapy options after progression on an AI include switching to another endocrine therapy (including fulvestrant), or everolimus plus exemestane (after anastrozole or letrozole only). 41,58,73,74 Evidence from clinical trials indicates that following progression with a nonsteroidal AI (anastrozole or letrozole), it is possible to obtain clinical benefit with a steroidal AI (exemestane) and vice versa. [75][76][77] Other endocrine options after progression on an AI include fulvestrant or tamoxifen.…”
Section: Current Treatment Options For Advanced/ Metastatic Breast Camentioning
confidence: 99%